2008
DOI: 10.1017/s146114570700836x
|View full text |Cite
|
Sign up to set email alerts
|

Retention rate and substance use in methadone and buprenorphine maintenance therapy and predictors of outcome: results from a randomized study

Abstract: This was a 6-month, randomized, flexible-dose study comparing the effects of methadone (Meth) and buprenorphine (Bup) on retention rate and substance use in a sample of 140 opioid-dependent, primarily heroin-addicted, patients who had been without opioid substitution therapy in the 4 weeks prior to the study. The major aims were to compare the efficacy of Bup and Meth in a flexible dosing regimen and to identify possible predictors of outcome. There were no major inhomogeneities between treatment groups. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
101
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 46 publications
19
101
1
2
Order By: Relevance
“…One of the important findings of the present study was that, while craving and withdrawal were higher in the group with a negative outcome, the mean dose of BN for stabilization did not differ between the groups. The mean dose of BN in the first 2 weeks was not associated with outcome, similar to the findings in patients treated with comparable mean daily doses of 9-12 mg 35,37,62 . In one observational study, initial induction doses of 16 mg were associated with better retention 38 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…One of the important findings of the present study was that, while craving and withdrawal were higher in the group with a negative outcome, the mean dose of BN for stabilization did not differ between the groups. The mean dose of BN in the first 2 weeks was not associated with outcome, similar to the findings in patients treated with comparable mean daily doses of 9-12 mg 35,37,62 . In one observational study, initial induction doses of 16 mg were associated with better retention 38 .…”
Section: Discussionsupporting
confidence: 78%
“…Finally in a recent study Schwarz et al 28 reported that over one third (37.2%) of the sample discontinued BN maintenance treatment within the first month following induction, while 25% of the sample stayed for at least 43 months in treatment 28 . There are few studies of OMT outcomes that consider what factors might be associated with treatment dropout or what might be done to i m p r ov e d r o p o u t r a t e s. P r e -t r e a t m e n t characteristics, most consistently associated with poorer outcome among heroin dependent patients in BN maintenance treatment, include; male gender, lack of employment, younger age at onset of opioid use, more continuous and longer opioid use, use of heroin rather than other opioids as the primary drug, higher levels of psychiatric symptoms, lower levels of general functioning, poorer psychosocial functioning and more severe legal problems 14,[29][30][31][32][33][34][35][36] . However, depression was associated with treatment retention in two studies 34,37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, medical management of OUD with buprenorphine/naloxone or methadone is often perceived as substituting one addiction for another. This misunderstanding of the contribution of medications to the overall management of OUD can lead to premature discontinuation of medication to the detriment of the patient, and thus, high rates of relapse [19,15,16,20]. Consider the Diagnostic and Statistical Manual of Mental Disorders criteria for the diagnosis of OUD (Figure 1).…”
Section: Measuring Treatment "Success"mentioning
confidence: 99%
“…43 It keeps patients in treatment and decreases heroin use and related crime and health problems. 44 However, heroin users often drink alcohol excessively.…”
Section: Discussionmentioning
confidence: 99%